Produktivitas Lahan Sawah Dalam Pemenuhan Kebutuhan Beras Penduduk - Ade Irma; La Ode Amaluddin; Surdin (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2022)
Planning and managing good and efficient land use are very important because they can indirectly support soil fertility and maintain stable land productivity. The research objectives were to: 1) find out how much rice production was in Andoolo Barat District in 2015-2019; and 2) know the level of productivity of paddy fields in Andoolo Barat District in 2015-2019. This study uses Mixed Methods in analyzing rice production. The results showed that rice production in 2015-2019 increased by 73.08 tons. While the productivity of paddy fields, when viewed from the carrying capacity of agricultural land, also experienced a surplus with a value of α > 1. This shows that the population's demand for rice is classified as optimal and fulfilled.